2016
DOI: 10.1007/s13594-016-0291-4
|View full text |Cite
|
Sign up to set email alerts
|

Formation of volatile compounds, peptidolysis and carbohydrate fermentation by mesophilic lactobacilli and streptoccocci cultures in a cheese extract

Abstract: Many studies about the influence of Lactococcus lactis on cheese flavour have been reported, while the impact of mesophilic lactobacilli and Streptococcus thermophilus, either as single or mixed cultures, have been less studied. The ability of Lactobacillus paracasei 90, Lb. casei 72 (INLAIN collection) and S. thermophilus 2 (commercial strain) to produce flavour-related biochemical changes, as single or mixed (lactobacilli + streptococci) cultures, was assessed in a cheese model. These three strains, with dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…At the beginning of sufu fermentation, microorganism metabolism tended to be vigorous, leading to high lipolysis and proteolysis. However, the total content of acids was significantly reduced during postfermentation, probably as they transformed into other compounds, such as esters (Peralta, Wolf, Perotti, Bergamini, & Hynes, ).…”
Section: Resultsmentioning
confidence: 99%
“…At the beginning of sufu fermentation, microorganism metabolism tended to be vigorous, leading to high lipolysis and proteolysis. However, the total content of acids was significantly reduced during postfermentation, probably as they transformed into other compounds, such as esters (Peralta, Wolf, Perotti, Bergamini, & Hynes, ).…”
Section: Resultsmentioning
confidence: 99%
“…3-hydroxy butan-2-one is an important aroma compound in grana cheeses, which can be produced by the action of mesophilic bacteria (Fox et al 2000). Peralta et al (2016) demonstrated the ability of Lp90 to produce this compound in a hard cheese extract. In addition, Wa and Ma cheeses had higher levels of acetic acid; a similar effect of Lp90 was previously observed in Cremoso cheese and in a soft cheese extract (Milesi et al 2010; Peralta et al 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Peralta et al (2016) demonstrated the ability of Lp90 to produce this compound in a hard cheese extract. In addition, Wa and Ma cheeses had higher levels of acetic acid; a similar effect of Lp90 was previously observed in Cremoso cheese and in a soft cheese extract (Milesi et al 2010; Peralta et al 2016). Lp90 strain showed a tendency to metabolize 2-methyl-propan-1-ol, 2-methylpropanoic and 3-methylbutanoic acids as their area values were lower in cheeses added with Lp90; this effect depended on the growth medium used for the culture preparation.…”
Section: Resultsmentioning
confidence: 99%
“…A direct correlation between the concentration of FAA and cheese flavor cannot be established, since different types of cheeses have similar relative proportions of amino acids, but differ distinctly in flavor (Sousa et al, 2001 ). In addition, as metabolism of amino acids seems to be strain-specific, a similar pool of FAA will be converted to different volatiles by different strains (Peralta et al, 2016 ). In this study, a limited differentiation of cheeses was observed based on FAA levels.…”
Section: Discussionmentioning
confidence: 99%